Experimental Assessment of Hole Quality and Tool Condition in the Machining of an Aerospace Alloy - Muhammad Aamir; Aamer Sharif; Muhammad Zeeshan Zahir; Khaled Giasin; Majid Tolouei-Rad (Machines, 2023)
This paper deals with an experimental investigation of hole quality in Al2024-T3, which is one of the aerospace alloys used in aircraft fuselage skin due to its high level of resistance to fatigue crack propagation. The experiments are conducted with 6 mm uncoated carbide and HSS drill bits using a CNC machine under dry conditions and different drilling parameters. The characteristics of the hole quality are investigated in terms of its perpendicularity, cylindricity, circularity and hole size. An ANOVA (analysis of variance) and Pareto charts are used to analyze the effects of the drilling parameters on the hole quality. The hole quality is also assessed using a digital microscope to observe the formation of hole burrs. Moreover, scanning electron microscopy is also used to investigate the inside-hole surface defects. Further investigations are carried out using optical microscopy to inspect the post-drilling tool condition at high drilling parameters. The results show that hole quality reduces as the feed rate and spindle speed increase. However, from the ANOVA results and Pareto charts, the influence of the feed rate on the hole quality is found to be insignificant. At the same time, the type of drill bit material shows the highest percentage of contribution affecting the hole quality, following the spindle speed. The HSS drill bit shows more adhesion and built-up edges than the uncoated carbide drill bit. There were more burrs formed at the hole edges when the holes were drilled with uncoated HSS drill bits. In the same way, the SEM analysis reveals more surface deformation and damage defects inside the hole walls of holes drilled using the uncoated HSS drill bit.